Workshop Penyusunan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing untuk Meningkatkan Keterampilan Proses Sains: Workshop on Preparing Student Worksheets (LKPD) Based on Guided Inquiry to Improve Science Process Skills - Abdul Gani; Nasrullah; Irwan Yon Hadi; Sukranudin (Pendidikan Al-Gafari, 2025)
This study investigates the effectiveness of guided inquiry-based worksheet development workshops in enhancing teachers’ pedagogical competence and instructional innovation in chemistry education. The primary objective was to evaluate both cognitive and attitudinal changes among teachers following structured training. A mixed-methods design was employed, combining pre- and post-tests with in-depth interviews to provide a comprehensive assessment of training outcomes. Quantitative analysis using paired t-tests demonstrated a significant improvement in teachers’ knowledge and skills in designing guided inquiry-based worksheets. Qualitative findings supported these results, highlighting increased confidence, positive attitudes toward student-centered learning, and the recognition of inquiry as a powerful approach to foster active engagement. The integration of both data sources revealed that the workshops not only improved technical competence but also shaped reflective practices and motivation for pedagogical renewal. These findings underscore the potential of guided inquiry-based training to strengthen teacher professionalism and to contribute to the broader advancement of innovative practices in science education. Future research is encouraged to explore larger populations and long-term impacts to ensure sustainability of the training outcomes.